Delivery of miR-26a Using an Exosomes-Based Nanosystem Inhibited Proliferation of Hepatocellular Carcinoma - Mahati, Shaya; Fu, Xiangjun; Ma, Xuexian; Zhang, Hua; Xiao, Lei (Frontiers in Molecular Biosciences, 2021)
Background: MicroRNA (abbreviated miRNA)-based treatment holds great promise for application as clinical antitumor therapy, but good carriers for delivery of the miRNA drug are lacking. Exosomes secreted by mesenchymal stem cells (MSCs) have proved to be safe, and exogenously modified exosomes may potentially represent an excellent drug delivery vehicle. Methods: In this study, we designed a delivery nano system using single-stranded variable fragment (scFv)-modified exosomes derived from human cord blood MSCs. Genetic engineering technology was used to obtain anti-Glypican 3 (GPC3) scFv-modified exosomes, which were then loaded with miR-26a mimics through electroporation. Results: Results of electron microscopy and dynamic light scattering indicated that the diameter of the drug-carrying exosomes was about 160 nm. Furthermore, anti-GPC3 scFv-modified exosomes effectively delivered miR-26a to GPC3-positive hepatocellular carcinoma cells, thereby inhibiting cell proliferation and migration by regulating the expression of downstream target genes of miR-26a. The exosomes-based nano system displayed favorable anti-tumor effect in vivo with no obvious side effects. Conclusion: Our data provided a new perspective for the use of exosome delivery systems for miRNA-based antitumor therapy.